THE INFLUENCE OF THE QUALITY OF SERVICE TOWARDS MANAGERS' PERFORMANCE OF MERTANADI AGRICULTURE COOPERATIVE IN PLAGA VILLAGE, PETANG DISTRICT, BADUNG REGENCY - Artini, Ni Wayan Putu; Ustriyana, I Nyoman Gede (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol.13, No.1, 2019DO - 10.24843/SOCA.2019.v13.i01.p07, 2019)
The purpose of this study is to analyze the relationship between service quality on the performance of cooperative administrators. The study was carried out at Koperasi Tani Mertanadi, Plaga Village, Petang Badung Subdistrict, with 60 respondents of simple cooperative members selected randomly. Analysis method using SEM-PLS. The results showed that there was a positive relationship between service and the performance of the cooperative management. The most influential indicator on service is the willingness of employees to understand the needs of members, while for performance variables, the indicator is the ability of supervisors to report the results of the Annual Member Meeting (RAT).